Design and fabrication of jig for butt welding - Mohd Rosyazwan Hanif, Ishak (2012)
The title of this final year project is “design and fabrication of jig for butt welding”. Jigs are special purpose tools which are used to facilitate production like machining, assembling and inspection operations. The purpose of this jig is to hold the specimen of the welding specimen which is the sheet metal. The fabrication purpose is to improve the quality of welding by making the better jig compare to the older jig. The students use this jig to hold the specimen and welding it by using the MIG welding at the welding machine. The problems are the specimen is bending after welding because affect by thermal stress. The older clamp cannot hold the specimen properly. This jig must be suitable to place on the existed table. The main objective of this study is to design and fabricate jig for butt welding. Also the objective is the jig need to suitable for hold sheet metal. Four designs were drew and compared in terms of durability, cost, size and weight, easy to use and clamping force. The best design is chosen and fabrication according to the measurement. After testing the product, the clamp has improves the clamping force and the specimen is not bending and affect by the thermal stress.